The implementation of Preview, Question, Read, Summarize and Test (PQRST) technique for students’ reading comprehension in the second grade of junior high school - Shelina Rynaldo, Agnessi; Sukirlan, Muhammad; Shafwati, Dian (U-Jet Unila Journal of English Language Teaching, 2025)
This study aims to find out whether the PQRST (Preview, Question, Read, Summarize, and Test) technique can improve reading comprehension of the students in the second grade of junior high school at SMP YBL Natar. The data were collected using a reading comprehension test, which was used to measure students’ performance before and after the technique was applied. The results showed a clear improvement. The average score increased from 65.30 on the pre-test to 74.50 on the post-test, with a gain of 9.20 points. A paired samples t-test was used to analyze the data, and the result was statistically significant at the 0.05 level (p < 0.05). Based on these findings, it can be concluded that the PQRST technique is effective in improving students’ reading comprehension.